2016
DOI: 10.1155/2016/7162313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride on Tensile and Bending Capacities of Basalt FRP Mesh Reinforced Cementitious Thin Plates under Indoor and Marine Environments

Abstract: This paper presented a durability experimental study for thin basalt fiber reinforced polymer (BFRP) mesh reinforced cementitious plates under indoor and marine environment. The marine environment was simulated by wetting/drying cycles (wetting in salt water and drying in hot air). After 12 months of exposure, the effects of the chloride on the tensile and bending behaviors of the thin plate were investigated. In addition to the penetration of salt water, the chloride in the thin plate could be also from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…It is shown that the systems reinforced with basalt fibers have high resistance to these aggressive influences. A similar comparison is made in [11][12][13] and it is shown that the tensile, bending and shear strength limits and modulus of elasticity are not inferior to GRP in their resistance. In [14][15][16] the resistance of basalt-plastic materials to low, high temperatures and thermocycles has been investigated and the stability of these materials to the specified effects has been shown.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…It is shown that the systems reinforced with basalt fibers have high resistance to these aggressive influences. A similar comparison is made in [11][12][13] and it is shown that the tensile, bending and shear strength limits and modulus of elasticity are not inferior to GRP in their resistance. In [14][15][16] the resistance of basalt-plastic materials to low, high temperatures and thermocycles has been investigated and the stability of these materials to the specified effects has been shown.…”
Section: Introductionsupporting
confidence: 70%
“…Advantages of polymeric materials reinforced with basalt fibers in terms of mechanical parameters, cost, resistance to aggressive environments, biological resistance are discussed in a number of works [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that systems reinforced by basalt fibers have high resistance to these aggressive influences. A similar comparison was made in [5, 6, 7] and it is shown that the ultimate tensile strength, ultimate bending strength, ultimate shear strength, and moduli of elasticity in tension, bending and shear are not inferior in their durability to the glass-reinforced plastics. In [8, 9, 10], resistance of basalt plastics to the action of low, high temperatures and thermal cycles was studied and stability of these materials to the indicated effects was shown.…”
Section: Introductionsupporting
confidence: 61%
“…The basalt plastic armature of periodic profile (BPA) is used in construction of industrial structures, electric power facilities, in road construction, in light arched building structures, to which demands for climatic and corrosion resistance are made. Advantages of polymeric materials reinforced with basalt fibers are discussed in a number of works [1, 2, 3, 4, 5, 6, 7, 8, 9, 10] according to mechanical parameters, cost, resistance to aggressive environments, and biological resistance.…”
Section: Introductionmentioning
confidence: 99%